Social policies, neoliberalism and individualization in the periphery of São Paulo - de Lima Jurca, Ricardo; Ianni, Aurea Maira Zöllner (Revista de Sociología, 2019)
The present article explores the expansion of the public and private health segment in response to the needs of the population of a peripheral sector of the South Zone of São Paulo, Brazil. Management of the sector is led from the margins of the capitalist peripheral State in the context of the current crisis of democracy which is driving a gradual individualization of social policies. As such, this management is both social and structural in nature. In addition to those users of the system who were interviewed, participants in the research included social leaders, Basic Health Unit (UBS) professionals, and agents of the Family Health Strategy (ESF) primary healthcare program. We focus on the continuities and discontinuities of public policies and highlight the important role that strategies of containment and reproduction of poverty have played in the process of legitimizing the democratic regime in Brazil.